2021
DOI: 10.1007/s10943-021-01460-x
|View full text |Cite
|
Sign up to set email alerts
|

Examining Factors Associated with Utilization of Chaplains in the Acute Care Setting

Abstract: Hospitalized persons want their spiritual needs addressed and discussed by the healthcare team, but medical providers and nurses lack the necessary training. Patients want chaplaincy care, but very few receive it, and little is known about utilization factors. To identify the population characteristics associated with the utilization of chaplaincy services, hospitalization data from March 2012 to July 2017 were analyzed (N = 15,242 patients). Religiously affiliated individuals and those with the most acute hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
2
1
Order By: Relevance
“…Unlike other studies suggesting that more female patients were visited by chaplains than male patients (White et al 2021 ; Choi et al, 2015 ), the current study did not show robust gender differences between those who received chaplain visits and the overall hospital population. Those who received chaplain visits were largely Christian, white, and skewed toward an older age group (Tables 1 and 2 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike other studies suggesting that more female patients were visited by chaplains than male patients (White et al 2021 ; Choi et al, 2015 ), the current study did not show robust gender differences between those who received chaplain visits and the overall hospital population. Those who received chaplain visits were largely Christian, white, and skewed toward an older age group (Tables 1 and 2 ).…”
Section: Discussioncontrasting
confidence: 99%
“…One such factor is biological sex. Studies indicate that women are more likely to receive spiritual care (White et al, 2021 ) and that there may be greater chaplaincy utilization among women than men, although the latter finding was derived from small groups of patients (Stang, 2017 ). Another study based on 30,995 chaplain visits from 1994 to 1996 indicated that patients’ religious affiliation was also related to their chaplaincy visits (Handzo et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the level of perceived professional benefit among nurses was positive in our study, SCC was at a moderate level, which may be due to the heavy workload among nurses and the lack of time (Anandarajah et al, 2021; López‐Tarrida et al, 2021; Yildirim & Ertem, 2022) and energy to provide spiritual care for patients. In addition, hospitals at all levels do not attach enough importance to spiritual care, with a lack of positive publicity, lack of training related to spiritual care, resulting in difficulties with the implementation of spiritual care (Best et al, 2022; White et al, 2022). In addition, current spiritual care training in China has yet to be perfected in comparison with that in other countries.…”
Section: Discussionmentioning
confidence: 99%